2020
DOI: 10.4999/uhod.204716
|View full text |Cite
|
Sign up to set email alerts
|

Single Center Experience on Screening Oncology Patients for Covid-19 Before Anti-Cancer Treatment

Abstract: The most important factor in the transmission of the COVID-19 is asymptomatic carriers. We’ve tested all oncology patients , that receive anti-cancer therapy, for COVID-19. We aimed to determine the rate of asymptomatic carriers, and analyze the clinical and ra- diological findings of infected patients. Oncology patients who have indications of receiving anti-cancer treatment in the hospital were tested for COVID-19, two day prior to their treatment even if they were asymptomatic by collecting nasopharyngeal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
1
2
Order By: Relevance
“…Seven (46%) of the 15 patients we identified with the PCR test died from COVID-19. Similar mortality rates have been reported in the study of Acar et al (%46,5). 6 In the study of Namal et al, only 1 of 28 COVİD-19 infected patients died.…”
Section: International Journal Of Hematology and Oncologysupporting
confidence: 86%
See 3 more Smart Citations
“…Seven (46%) of the 15 patients we identified with the PCR test died from COVID-19. Similar mortality rates have been reported in the study of Acar et al (%46,5). 6 In the study of Namal et al, only 1 of 28 COVİD-19 infected patients died.…”
Section: International Journal Of Hematology and Oncologysupporting
confidence: 86%
“…4 Namal et al, found 8.9% COV-ID-19 positivity when they screened 312 patients before chemotherapy and 89.3% of them were asymptomatic. 5 In Namal's study infection rate and the asymptomatic infection rate were higher compared to our study. The authors suggested that this high rate of asymptomatic infection may be a reflection of the immune-suppressive condition of cancer patients.…”
Section: International Journal Of Hematology and Oncologycontrasting
confidence: 69%
See 2 more Smart Citations